Language Experience and Phonetic Training as Factors Influencing Timing Organisation in Polish Learners of English - Gralińska-Brawata, Anna (Research in Language, 2014)
The paper investigates the dynamics of speech rhythm in Polish learners of English and, specifically, how rhythm measurements revealing durational characteristics of vocalic and consonantal intervals through the measures (%V, ΔV, ΔC, VarcoV, VarcoC and nPVI) change along the process of second language acquisition as a result of language experience and phonetic training, and influence rhythmic characteristics of L2 English. The data used for the analysis come from 30 Polish first-year students of the University of Łódź recorded reading two texts (English and Polish) during two recording sessions separated by a 7-month period of language studies and compared to the data obtained from the recordings of native speakers of English. The experiment aims at verifying whether the participants achieve progress in the rhythm measure scores under the influence of language experience and phonetic training, as it has already been confirmed that general proficiency of non-native speakers of English is a key factor contributing to the successful production of rhythmic patterns in English (Waniek-Klimczak 2009, Roach 2002). The results have shown no substantial and consistent progress for the whole group and across all the measures. Statistical tests, however, have revealed significant changes in the subjects’ performance with respect to the vocalic measures ΔV and VarcoV. This may reflect the effect of the type of phonetic training the students are offered, which is segment-based with particular emphasis on vowels.